Research discussion paper - Australian Institute of Aboriginal and Torres Strait Islander Studies (Canberra, A.C.T. : Aboriginal Studies Press, 1995)
The AIATSIS Research Discussion Papers series contributes to a greater understanding of contemporary issues in Indigenous studies, introducing new research topics and innovative approaches. Discussion papers are of a high scholarly standard, are informed by relevant research and may locate the topic within policy frameworks. They are anonymously peer reviewed by at least two independent experts and are between 7000 to 20,000 words in length.
Each issue has a distinctive title.
Some issues available only in online format.
Also available in an electronic version via the Internet. Address as at 25/7/14: http://www.aiatsis.gov.au/research/discussionpapers.html
Keywords: Aboriginal Australians; Aboriginal Australians -- Research; Australian